Autoimmune Hemolytic Anemia as Presentation of Celiac Disease - Ahmed Abdul Hadi Mohsen; Hiba Sadiq Mohammed Hassan; Ahmed Mohamad Mechi; Alaa Jumaah Manji Nasrawi (مجلة الكوفة الطبية)
Celiac disease is a multisystem disorder in children and adults; it is considered as one of the most important malabsorption syndromes related to an auto-immune mediated response to gluten-containing food in a genetically predisposed patient. The most common involved system is the Gastrointestinal tract. Association with other autoimmune diseases such as thyroid disease and diabetes mellitus type 1 is well known but autoimmune mediated hemolytic anemia that responded to a gluten-free diet was interesting to be found.